Bacillus velezensis CLA178-Induced Systemic Resistance of Rosa multiflora Against Crown Gall Disease - Chen, Lin; Wang, Xinghong; Ma, Qinghua; Bian, Lusen; Liu, Xue; Xu, Yan; Zhang, Huihui; Shao, Jiahui; Liu, Yunpeng (Frontiers in Microbiology, 2020)
Plant growth-promoting rhizobacteria (PGPRs) are able to activate induced systemic resistance (ISR) of the plants against phytopathogens. However, whether and how ISR can be activated by PGPRs in plants of the Rosa genus is unclear. The effects of PGPR Bacillus velezensis CLA178 and the pathogen Agrobacterium tumefaciens C58 on the growth, plant defense-related genes, hormones, and reactive oxygen species (ROS) in the rose plants were compared. Pretreatment with CLA178 significantly reduced crown gall tumor biomass and relieved the negative effects of the C58 pathogen on plant biomass, chlorophyll content, and photosynthesis of roses. Pretreatment of the roots with CLA178 activated ISR and significantly reduced disease severity. Pretreatment with CLA178 enhanced plant defense response to C58, including the accumulation of ROS, antioxidants, and plant hormones. Moreover, pretreatment with CLA178 enhanced C58-dependent induction of the expression of the genes related to the salicylic acid (SA) or ethylene (ET) signaling pathways. This result suggested that SA- and ET-signaling may participate in CLA178-mediated ISR in roses. Additional experiments in the Arabidopsis mutants showed that CLA178 triggered ISR against C58 in the pad4 and jar1 mutants and not in the etr1 and npr1 mutants. The ISR phenotypes of the Arabidopsis mutants indicated that CLA178-mediated ISR is dependent on the ET-signaling pathway in an NPR1-dependent manner. Overall, this study provides useful information to expand the application of PGPRs to protect the plants of the Rosa genus from phytopathogens.